2015
DOI: 10.33549/physiolres.932772
|View full text |Cite
|
Sign up to set email alerts
|

Captopril Partially Decreases the Effect of H2S on Rat Blood Pressure and Inhibits H2S-Induced Nitric Oxide Release From S-Nitrosoglutathione

Abstract: We studied the effects of the H 2 S donor Na 2 S on the mean arterial blood pressure (MAP) and heart and breathing rates of anesthetized Wistar rats in the presence and absence of captopril. Bolus administration of Na 2 S (1-4 µmol/kg) into the right jugular vein transiently decreased heart and increased breathing rates; at 8-30 µmol/kg, Na 2 S had a biphasic effect, transiently decreasing and increasing MAP, while transiently decreasing heart rate and increasing and decreasing breathing rate. These results ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
4
17
0
Order By: Relevance
“…Slow H 2 S-donor AP39 decreased and consequently increased blood pressure at 0.2-1.0 µmol/kg . Our in vivo experiments showed that intravenously injected Na 2 S (3 μmol/kg) had vasopressor effects only; however, at higher Na 2 S doses (8-30 μmol/kg), we demonstrated a transient biphasic effect on blood pressure (Drobna et al 2015). The K ATP channel has been reported to be a major molecular target of the vasorelaxant and vasodepressor effects of H 2 S (Zhao et al 2001).…”
Section: H 2 S In Hypertensionmentioning
confidence: 62%
See 4 more Smart Citations
“…Slow H 2 S-donor AP39 decreased and consequently increased blood pressure at 0.2-1.0 µmol/kg . Our in vivo experiments showed that intravenously injected Na 2 S (3 μmol/kg) had vasopressor effects only; however, at higher Na 2 S doses (8-30 μmol/kg), we demonstrated a transient biphasic effect on blood pressure (Drobna et al 2015). The K ATP channel has been reported to be a major molecular target of the vasorelaxant and vasodepressor effects of H 2 S (Zhao et al 2001).…”
Section: H 2 S In Hypertensionmentioning
confidence: 62%
“…We confirmed this finding using glibenclamide, a K ATP channel inhibitor. Specifically, this inhibitor blocked the vasorelaxation induced by higher doses of H 2 S (Drobna et al 2015). Given that 1) acute pretreatment with glibenclamide did not affect low-dose H 2 S-induced contractile responses of isolated thoracic aortas and 2) the increase in blood pressure was observed at lower H 2 S concentrations than the biphasic effects, we concluded that K ATP channels were not involved in the transient blood pressure increase.…”
Section: H 2 S In Hypertensionmentioning
confidence: 76%
See 3 more Smart Citations